2006
DOI: 10.1007/s10143-006-0021-0
|View full text |Cite
|
Sign up to set email alerts
|

A pituitary abscess showing high signal intensity on diffusion-weighted imaging

Abstract: The utility of diffusion-weighted imaging (DWI) for the diagnosis of intracranial abscesses has already been established. However, the use of DWI for pituitary abscesses has not been previously reported. We present a case of postoperative pituitary abscess in which T1-weighted and T2-weighted magnetic resonance imaging (MRI) revealed a supra-sellar cystic mass, with the cyst contents showing high intensity on DWI. This case suggests that DWI is useful for the diagnosis of pituitary abscesses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 10 publications
1
24
0
6
Order By: Relevance
“…The majority of the previously reported cases of RCC abscess have presented with clinical features typical of mass effect, namely; visual impairment, endocrine disturbance and headache [3]. Systemic features such as leukocytosis and pyrexia are atypical but may also manifest [35]. The majority of RCC abscesses seem to occur spontaneously, although previous pituitary surgery, irradiation of the gland and immunosuppressive therapy are speculated to be risk factors [1, 2].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the previously reported cases of RCC abscess have presented with clinical features typical of mass effect, namely; visual impairment, endocrine disturbance and headache [3]. Systemic features such as leukocytosis and pyrexia are atypical but may also manifest [35]. The majority of RCC abscesses seem to occur spontaneously, although previous pituitary surgery, irradiation of the gland and immunosuppressive therapy are speculated to be risk factors [1, 2].…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that pituitary apoplexy occasionally demonstrates ring enhancement after gadolinium injection 1 . Pituitary abscess has also been reported to show high signal intensity on diffusion-weighted imaging (DWI) 1,17,18 . On the other hand, pituitary apoplexy also demonstrates high signal intensity on DWI due to ischemic injury or deposit of blood derived substances.…”
Section: Discussionmentioning
confidence: 96%
“…2,3,[7][8][9][12][13][14]16,17,19,[21][22][23][24]26) Twelve patients were female, seven were male, and the mean age of these patients was 44.1 years (range 12-69 years). Three were pediatric cases.…”
Section: Discussionmentioning
confidence: 99%